(untitled) (University of Khartoum Engineering Journal, 2022)
This study aims to predict swelling pressure in compacted clay from given soil index parameters such as dry density, water content, void ratio, clay content and plasticity index. Three different clay samples were prepared with varying water contents and dry densities. The swell-consolidation method was used to measure the swelling pressure, Ps. Analysis of the tests results demonstrates very clearly a strong linear relationship of Ps with the Factor of initial soil state, Fi, combination of water content, dry density and void ratio. The coefficients of this linear relationship (i.e. constant and slope) were found to depend on plasticity index and clay content. It is shown that predicted values of swelling pressure obtained from the proposed relationship agree closely with the experimental results of this study and those reported in the literature.